Study of Glazes and Their Effects on Properties of Triaxial Electrical Porcelains from Ugandan Minerals - Olupot, Peter W.; Jonsson, Stefan; Byaruhanga, Joseph K. (Journal of Materials engineering and performance, 2010)
Kaolin, ball clay, feldspar, and sand were collected from deposits in Uganda, milled and sieved to particle sizes of 45, 45, 53, and 25 μm, respectively. Three porcelain bodies and five glazes were formulated from them. The glazes were applied on porcelain specimens and subsequently evaluated for their effects on properties of porcelain samples. The formulated specimens were investigated using dilatometry, Steger test, FEG-SEM, XRD, 4-point bending, dielectric strength, and fracture toughness tests. A porcelain specimen consisting of 68% SiO2, 19% Al2O3, 4.7% K2O, and a glaze RO:0.57Al2O3:4.86SiO2 exhibited MOR of 105 MPa with Weibull modulus of 5.6 and a dielectric strength of 18 kV/mm upon firing at a heating rate of 6 °C/min to 1250 °C and holding for 2 h. The microstructure of the high-strength specimen exhibited round mullite needles, quartz, and glass. Holding samples for 2 h at peak temperature resulted in a 22% increase in MOR compared to 1 h holding. Glazing further improved strength by 67% for the best sample. Compressive stresses in glaze contributed to the strengthening effect. The dielectric and mechanical strength values obtained qualify the formulated sample for application in electrical insulation.
Keywords: advanced characterization; chemical analysis; electron microscopy; mechanical testing; structural ceramics